Age‐related difference of the association of cardiovascular risk factors with the cardio‐ankle vascular index in the Cardiovascular Prognostic Coupling Study in Japan (the Coupling Registry). Issue 7 (12th June 2020) - Kabutoya, Tomoyuki; Hoshide, Satoshi; Fujiwara, Takeshi; Negishi, Keita; Nishizawa, Masafumi; Yamamoto, Mitsuyoshi; Yamagiwa, Kayo; Kawashima, Akihiro; Yoshida, Tetsuro; Nakazato, Jun; Matsui, Yoshio; Sekizuka, Hiromitsu; et al.
Abstract: The value of the cardio‐ankle vascular index (CAVI) increases with age. All large‐scale studies of the CAVI have investigated patients <80 years old. Thus, the clinical characteristics of high CAVI in patients aged 80 or more remain unclear. Therefore, we investigated (1) the CAVI in very elderly patients and (2) the determinants of a high CAVI in high‐risk patients, including very elderly patients. The Cardiovascular Prognostic Coupling Study in Japan (Coupling Registry) is a prospective observational study of Japanese outpatients with any cardiovascular risk factors. We enrolled 5109 patients from 30 institutions (average age 68.7 ± 11.4 years, 52.4% males). We investigated the determinants of the CAVI by separating the patients into three groups: 970 middle‐aged (<60 years), 3252 elderly (60‐79 years), and 887 very elderly (≥80 years) patients. The CAVI values of the males were significantly higher those of the females in all age groups (<60 years: 7.81 ± 1.11 vs. 7.38 ± 0.99, P < .001; 60‐79 years: 9.20 ± 1.29 vs. 8.66 ± 1.07, P < .001; ≥80 years: 10.26 ± 1.39 vs. 9.51 ± 1.12, P < .001). In all age groups, the CAVI of the patients with diabetes/glucose tolerance disorder was higher than that of the patients without diabetes/glucose tolerance disorder (<60 years: 7.82 ± 1.22 vs 7.58 ± 1.03, P = .002; 60‐79 years: 9.23 ± 1.20 vs 8.78 ± 1.19, P < .001; ≥80 years: 10.04 ± 1.24 vs 9.75 ± 1.32, P = .002). The determinants of the CAVI in these very elderly patients were age, male sex, low BMI, and mean blood pressure. Diabetes/glucose tolerance disorder and glucose were independently associated with the CAVI in the patients aged <60 years and 60‐79 years, but not in those aged ≥80 years after adjusting for other covariates.